A Comprehensive Analysis of In-Line Inspection Tools and Technologies for Steel Oil and Gas Pipelines - Parlak, Berke Ogulcan; Yavasoglu, Huseyin Ayhan (MDPI, 2023)
The transportation of oil and gas through pipelines is an integral aspect of the global energy infrastructure. It is crucial to ensure the safety and integrity of these pipelines, and one way to do so is by utilizing an inspection tool called a smart pig. This paper reviews various smart pigs used in steel oil and gas pipelines and classifies them according to pipeline structure, anomaly-detection capability, working principles, and application areas. The advantages and limitations of each sensor technology that can be used with the smart pig for in-line inspection (ILI) are discussed. In this context, ultrasonic testing (UT), electromagnetic acoustic transducer (EMAT), eddy current (EC), magnetic flux leakage (MFL), and mechanical contact (MC) sensors are investigated. This paper also provides a comprehensive analysis of the development chronology of these sensors in the literature. Additionally, combinations of relevant sensor technologies are compared for their accuracy in sizing anomaly depth, length, and width. In addition to their importance in maintaining the safety and reliability of pipelines, the use of ILI can also have environmental benefits. This study aims to further our understanding of the relationship between ILI and the environment.
Keywords: in-line inspection; smart pig; sensor; oil; natural gas; pipeline; environment; EXTERNAL CORROSION; NONDESTRUCTIVE INSPECTION; WAVELET TRANSFORM; DEFECT DETECTION; METAL-LOSS; PIPE; MODEL; EMAT; PIG; SYSTEM; Science & Technology - Other Topics; Environmental Sciences & Ecology